(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article explores the process of forming competitive advantages within enterprises, aiming to elucidate strategies and methodologies that foster organizational success in competitive markets. Through an in-depth analysis of various factors influencing competitive advantage development, including organizational culture, strategic planning, innovation, and market positioning, this study aims to provide valuable insights into enhancing the competitiveness of businesses. By identifying key determinants and leveraging opportunities effectively, enterprises can optimize their operations, differentiate themselves from competitors, and sustain long-term success in dynamic business environments.